DEVELOPMENT OF ACCOUNTING AND ANALYSIS METHODOLOGY OF INVESTMENTS IN HUMAN CAPITAL : Ochilov Olmos Ikrom ugli (Ustozlar uchun, 2024)
The article reveals issues of improving the accounting and analysis of human capital and investments in business entities. The interpretation of investments in human capital as an element of financial statements is explained and a methodology for their reflection in accounts and reports is proposed. When analyzing investments in human capital, an analysis of factors influencing the return on investment in employee training was carried out.